2009
DOI: 10.2478/s11535-009-0028-y
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of Cd2+ and ACh on action potentials of Nitellopsis obtusa cells

Abstract: Abstract:Interrelations between the action of acetylcholine (ACh) and cadmium ions (Cd 2+ ) on bioelectrogenesis of Nitellopsis obtusa cells were investigated. We analyzed repetitively triggered action potentials (AP), their reproducibility, shape and dynamics of membrane potential after AP induction. ACh significantly increased membrane permeability only at high concentrations (1 mM and 5 mM). Repolarisation level of action potential after the first stimulus was much more positive in all cells treated with AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Exposure of ACh to potassium K out or K in channels does not appear to exclude its action on the excitable chloride channels. We previously demonstrated [31] that the addition of ACh prolongs the repolarization of the action potential in 'pump state' cells just as Gong and Bisson have demonstrated in another Characeaen, Chara corallina [22]. They attributed this prolongation to the increased probability of the tonoplast chloride channels opening, which would tend to maintain cell in a more depolarized state.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Exposure of ACh to potassium K out or K in channels does not appear to exclude its action on the excitable chloride channels. We previously demonstrated [31] that the addition of ACh prolongs the repolarization of the action potential in 'pump state' cells just as Gong and Bisson have demonstrated in another Characeaen, Chara corallina [22]. They attributed this prolongation to the increased probability of the tonoplast chloride channels opening, which would tend to maintain cell in a more depolarized state.…”
Section: Discussionmentioning
confidence: 65%
“…This links ACh with numerous signalling processes in the so-called 'big network' of calcium signalling. In our previous work [31] we found that cadmium strengthens the depolarizing effect of acetylcholine on the repolarization phase of action potential and could be explained by an impact on the intracellular calcium level. The effect of ACh on the cytoplasmic Ca 2+ content requires a separate study.…”
Section: Discussionmentioning
confidence: 82%
“…The reference electrode was immersed into the experimental solution near the cell and the microelectrode was inserted into the cell to measure electrical potential differences between outside and inside the intermodal cell. The details of experimental procedures, parameters and specifications of the experimental techniques were thoroughly described in previous studies [13][14][15].…”
Section: Object and Methodsmentioning
confidence: 99%
“…All treated cells died after 2 h in 100 mM Cd 2+ solution (Kisnieriene et al 2009). Furthermore, electrical stimulation accelerated this process.…”
Section: Membrane Potential As An Indicator Of Early Effect Of Bioactmentioning
confidence: 97%